Physical Evidence (Tangibles) in Class III Inpatient Services at Sidoarjo Regency Hospital - Monicha, Mawar; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2021)
Improving public services organized by hospital agencies is often a community demand. In general, the cause is an imbalance between the number of service requests and the hospital's ability to meet these needs. As a result, service recipients often criticize the services they receive. This study aims to determine and analyze the Physical Evidence (tangibles) in Class III Inpatient Services Bhayangkara Pusdik Sabhara Porong Hospital, Sidoarjo Regency. This study used descriptive qualitative method. The results showed that physical evidence (tangibles) in Class III Inpatient Services at Bhayangkara Pusdik Sabhara Porong Hospital, Sidoarjo Regency was running quite well, in terms of the administrative service process that was not difficult, the condition of the sleeping facilities was quite good and comfortable, but still needs attention. and improved regarding the number of inadequate bed facilities, cleanliness and additional chairs for the patient's family.